2014
DOI: 10.1634/theoncologist.2014-0304
|View full text |Cite
|
Sign up to set email alerts
|

Drug Development for Hepatocellular Carcinoma: Knowing the Past Helps to Understand the Future

Abstract: Hepatocellular carcinoma (HCC) is a highly complicated disease characterized by comorbid cirrhosis and disease heterogeneity. Given multiple failures in the past, we need to learn from previous experiences and generate novel ideas to increase the chance of success. More effort and patience should be exercised in the selection of a homogeneous patient population and identification of predictive markers during drug development for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The traditional and old concept of chemotherapy unsuitable for HCC has met strong doubts, great challenges and changes. Now, new systemic combination chemotherapy with better response is another option for some advanced HCC patients with distal metastasis or patients who are not candidates for local/regional treatment [17]. Of course, systemic chemotherapy is only a means in the comprehensive treatment of advanced HCC, may only solve part of the problems, its effect is also limited.…”
Section: "Oxaliplatin-basedmentioning
confidence: 99%
“…The traditional and old concept of chemotherapy unsuitable for HCC has met strong doubts, great challenges and changes. Now, new systemic combination chemotherapy with better response is another option for some advanced HCC patients with distal metastasis or patients who are not candidates for local/regional treatment [17]. Of course, systemic chemotherapy is only a means in the comprehensive treatment of advanced HCC, may only solve part of the problems, its effect is also limited.…”
Section: "Oxaliplatin-basedmentioning
confidence: 99%
“…Unfortunately, the process of anti-HCC drug discovery and development seems to be very challenging and inefficient as reflected by the high attrition rate of drugs that enter preclinical testing but fail to gain FDA approval [7]. One of the underlying causes is the low predictive value of animal models of HCC that are used before in-human clinical trials are launched.…”
Section: Introductionmentioning
confidence: 99%
“…For example codrituzumab [5], Linifarib, Sunitinib, Brivanib , cixutumumab [6][7][8][9], Everolismus showed no significant increase in overall survival (OS). Only Sorafenib as shown in the SHARP (1) trial in the West and as shown in Oriental trial conducted in the East showed statistically significant (3 months) increase in OS [10][11][12][13][14].…”
Section: Systemic Therapies In Advanced Hepatocellular Cancermentioning
confidence: 99%